2007
DOI: 10.1161/hypertensionaha.107.095448
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cardiac Effects of Adrenalectomy or Mineralocorticoid Antagonists in Patients With Primary Aldosteronism

Abstract: Abstract-Exposure to excess aldosterone results in cardiac damage in hypertensive states. We evaluated the long-term cardiac structural and functional evolution in patients with primary aldosteronism after surgical or medical treatment. Fifty-four patients with primary aldosteronism were enrolled in a prospective study and were followed for a mean of 6.4 years after treatment with adrenalectomy (nϭ24) or spironolactone (nϭ30). At baseline, echocardiographic measurements of patients with primary aldosteronism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
235
2
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 313 publications
(257 citation statements)
references
References 60 publications
16
235
2
4
Order By: Relevance
“…In fact, LV mass decreased in both patients with higher and lower plasma aldosterone, but the degree of LV mass regression tended to be greater in the former group (21 versus 12%), suggesting, in this case, a direct involvement of aldosterone in the development of LV hypertrophy. These findings are in partial agreement with those of a long-term prospective study, 3 in which we reported significant reduction of LV mass to occur in 30 patients with primary hyperaldosteronism who were treated with spironolactone and in whom a multivariate analysis demonstrated that pretreatment aldosterone levels predict treatment-induced LV mass decrease independent of blood pressure change. In our study, however, decrease in LV mass was much slower that in Gaddam's study, reaching statistical significance only after a few years, and occurred in the absence of significant changes in cardiac and systemic markers of the volume status.…”
Section: Hyperaldosteronism and Left Ventricular Hypertrophysupporting
confidence: 91%
“…In fact, LV mass decreased in both patients with higher and lower plasma aldosterone, but the degree of LV mass regression tended to be greater in the former group (21 versus 12%), suggesting, in this case, a direct involvement of aldosterone in the development of LV hypertrophy. These findings are in partial agreement with those of a long-term prospective study, 3 in which we reported significant reduction of LV mass to occur in 30 patients with primary hyperaldosteronism who were treated with spironolactone and in whom a multivariate analysis demonstrated that pretreatment aldosterone levels predict treatment-induced LV mass decrease independent of blood pressure change. In our study, however, decrease in LV mass was much slower that in Gaddam's study, reaching statistical significance only after a few years, and occurred in the absence of significant changes in cardiac and systemic markers of the volume status.…”
Section: Hyperaldosteronism and Left Ventricular Hypertrophysupporting
confidence: 91%
“…Although mineralocorticoid receptor antagonists produced multi-directional anti-inflammatory effects, their monocyte-and lymphocyte-suppressive effects did not increase with time, and cytokine release was higher than in control subjects during the entire observation period. These findings are in disagreement with those of other authors [8][9][10] who observed similar cardiovascular and nephroprotective benefits after adrenalectomy and spironolactone treatment. However, their study populations included both patients with aldosteronoma (most of whom underwent adrenalectomy) and patients with bilateral adrenal hyperplasia (treated with spironolactone), and this fact may explain the differences between our results and their results.…”
contrasting
confidence: 99%
“…84 Spironolactone may appear to be less potent than adrenalectomy for improving left ventricular hypertrophy, but studies with long-term follow-up have shown that the same improvement is ultimately achieved, even though the regression of left ventricular mass is slower with spironolactone than with adrenalectomy. 29,34,85 The benefits of PA treatment were similar for specific drugs and surgery in both studies comparing the incidence of cardiovascular events in treated PA patients and matched controls with essential hypertension. 36,37 The relative glomerular hyperfiltration and microalbuminuria of PA patients are corrected on specific drugs (Figure 1).…”
Section: Outcomes Of Drug-based Treatmentmentioning
confidence: 85%
“…28 Many studies have shown that left ventricular mass decreases and that aortic pulse wave velocity and carotid intima-media thickness improve after adrenalectomy. [29][30][31][32][33][34][35] A prospective study compared cardiovascular events in 54 PA patients treated by adrenalectomy (unilateral disease) or with spironolactone (unilateral or bilateral disease) with 323 patients with essential hypertension. 36 The composite endpoint was myocardial infarction, stroke, any type of revascularization procedure, and sustained arrhythmia.…”
Section: Outcomes Of Adrenalectomy In Unilateral Pamentioning
confidence: 99%